Distribution of molekular-genetic markers at sportsmen - N А Rudyh; V V Sokorev; F I Sobjanin; I K Aristova; M I Churnosov (RUDN Journal of Medicine, 2009)
Results of research polymorphism carrier genes hSERT, ACE, DAT1 at sportsmen of marksmen are resulted. High frequencies of gene DAT1*10 and genotype DAT1*10/DAT1*10 at sportsmen in comparison with population, and also high frequency of heterozygotes (68,96%) on a gene ACE in comparison with population control (50,5%, p < 0,01) are established.